2013
DOI: 10.1016/j.bbamem.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fluidity and activity of membrane ATPases in human erythrocytes under the influence of polyhydroxylated fullerene

Abstract: The influence of fullerenol on the activities of human erythrocyte membrane ATPases and the fluidity of the plasma membrane as well as the possibility of fullerenol incorporation into the plasma membrane were investigated. Fullerenol at concentrations up to 150 μg/mL induced statistically significant decreases in the anisotropy of 1-anilino-8-naphthalene sulfonate (ANS) (14%), N,N,N-trimethyl-4-(6-phenyl-1,3,5,-hexatrien-1-yl)phenylammonium p-toluenesulfonate (TMA-DPH) (7.5%) and 1,6-diphenyl-1,3,5-hexatriene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…Presumably, hydrated C 60 fullerene nanoparticles influence protein and lipid components of the membrane, which, in turn, induce the change of the surface stiffness. The presence of hydroxyl groups on the surface of pristine C 60 fullerene in aqueous solution reported before by Prylutskyy et al (2014b) apparently allows C 60 fullerene to form numerous hydrogen bonds with protein domains and hydrophilic lipid ends of membrane (Grebowski et al 2013a). The association between hydroxylated C 60 fullerene and band three protein of human erythrocyte membrane has been proven experimentally (Grebowski et al 2013b).…”
Section: Discussionmentioning
confidence: 93%
“…Presumably, hydrated C 60 fullerene nanoparticles influence protein and lipid components of the membrane, which, in turn, induce the change of the surface stiffness. The presence of hydroxyl groups on the surface of pristine C 60 fullerene in aqueous solution reported before by Prylutskyy et al (2014b) apparently allows C 60 fullerene to form numerous hydrogen bonds with protein domains and hydrophilic lipid ends of membrane (Grebowski et al 2013a). The association between hydroxylated C 60 fullerene and band three protein of human erythrocyte membrane has been proven experimentally (Grebowski et al 2013b).…”
Section: Discussionmentioning
confidence: 93%
“…DPH and TMA-DPH were incorporated, according to partition equilibrium, in the hydrophilic layer at the membrane surface (TMA-DPH) and the hydrophobic core of the lipid bilayer (DPH). Steady-state florescence anisotropy of TMA-DPH reflected the packing of membrane lipid fatty acid chains and an increase in TMA-DPH anisotropy indicated a reduction in membrane fluidity in the region of the bilayer where the probe was incorporated (Grebowski, Krokosz, & Puchala, 2013;Lukyanenko et al, 2013).…”
Section: Effect Of Grape Pomace Extracts On Membrane Fluiditymentioning
confidence: 99%
“…The many hydroxyl groups present on the surface of fullerenol enable not only attachment of various compounds (including drug molecules), but also the creation of multiple hydrogen bonds with various components of biological systems (such as protein domains of the plasma membrane or hydrophilic lipid heads) [51]. Our experiments have shown that fullerenol can be adsorbed to erythrocyte cytoskeletal proteins [13] and this interaction can be used as a drug transport mechanism (Figure 3).…”
Section: Fullerenol and Chemotherapymentioning
confidence: 99%